(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article talks about the stages of the emergence and formation of folk art, the problems encountered in scientific research . In addition, necessary recommendations for teaching, re-research of Uzbek folklore, scientific study of epics are discussed in detail.